PROBLEMATIKA PENCATATAN PERKAWINAN PADA KUA SE-KOTA MADIUN DITINJAU DARI MAQASID SYARI’AH - Ahmad Mustofa; Marwa Maratus Sholeha; Moh. Anang Darwisyi (AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2023)
This article aims to find out the perceptions of KUA employees in the city of Madiun regarding underhand marriage. This is because there is still a dualism in understanding the validity of underhand marriage. So that gave rise to various problems of marriage registration at KUA in Madiun city. This research is a qualitative research with descriptive analysis method. The analysis technique used is exploratory technique. The results showed that in the city of Madiun the KUA agreed that marriages that were not administratively registered at the KUA were considered invalid under state law, especially when viewed from Maqaṣid as-Syari'ah who invited Hifẓu al-Din and Hifẓu al-Nasl , the state is in principle obliged to protect its people from damage to religion and heredity. With underhand marriage, it will have a physical and psychological impact on the rights of the wife and children. The wife cannot be called a legal wife according to state law. So that her rights as a wife are not guaranteed to be fulfilled. Then the impact of underhand marriage on the status of the child is only related civilly to the mother and/or the mother's family.